The Influence of Income and the Business Cycle on Birth Rates in Bulgaria, 2000-2016 - Kosuliev, Aleksandar (Research Papers, 2020)
In the last three decades the population of Bulgaria decreases, which poses a challenge for the country’s economic development. It is possible that the opposite relation – from economic to demographic processes – also exists.  Our analysis show that in Bulgaria income and the business cycle on one hand and the birth rate, on the other, are correlated for the period 2000-2016. Regardless of the initial income level, birth rate falls when the economy is in a crisis and it goes up when the economy recovers. However long-term increase in the birth rate as a reaction to long-term growth is questionable, as total birth rate remains unchanged. Instead, increases in the income level shift the birth rate from lower to higher age groups.
Keywords: Birth rate; Business cycle; Income; Bulgaria